The student journey in PBL: using individual portfolios to promote self-reflection and assessment as learning - Fernandes, Sandra (2022)
This paper aims to present findings based on students’ journey within a Project-based learning (PBL) experience, with particular emphasis on the development of an individual portfolio by students, as part of the assessment process. The PBL project involved three curricular units (Research Methods and Techniques II, Ethics and Education and Sociology of Education), from the field of Education Sciences, integrated in the first year of the study plan of the Social Education degree programme at Portucalense University, Portugal. This paper describes student assessment within this educational approach, including both formative and summative methods. It calls attention to the concept of assessment as learning, which can be understood as a process where students are able to learn about themselves as learners and take responsibility for their own learning and monitor future directions. One of the assessment methods included in the PBL approach is the development of an individual portfolio with the purpose of enhancing student self-reflection and assessment of their work on a regular basis. The portfolio allowed students to share evidence of the project journey, with particular focus on the student’s learning process. The students were provided with general guidelines to develop their portfolio, but the flexible nature of this educational resource allowed students to record and highlight their individual and team contributions in a very creative and personalized way. The analysis of qualitative data from the individual student portfolios reveals student self-reflection on individual achievements, project milestones, teamwork skills, impact of teacher feedback, celebration moments, amongst others. Implications of these findings for PBL assessment practices will be discussed further in the paper.